2009
DOI: 10.3748/wjg.15.5789
|View full text |Cite
|
Sign up to set email alerts
|

Role of the receptor for advanced glycation end products inhepatic fbrosis

Abstract: AIM:To study the role of advanced glycation end products (AGE) and their specific receptor (RAGE) in the pathogenesis of liver fibrogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 51 publications
(67 reference statements)
4
46
0
2
Order By: Relevance
“…Our results are also in line with prior findings in CCl4-induced hepatic fibrosis where RAGE transcript and protein levels were upregulated until 6 weeks after the completion of CCl4 treatment [32]. Furthermore, it has been shown that α-SMA-positive HSC/myofibroblasts of the septal or portal interface, representing the prominent fibrogenic effectors, expressed RAGE in both fibrosis models.…”
Section: Discussionsupporting
confidence: 81%
“…Our results are also in line with prior findings in CCl4-induced hepatic fibrosis where RAGE transcript and protein levels were upregulated until 6 weeks after the completion of CCl4 treatment [32]. Furthermore, it has been shown that α-SMA-positive HSC/myofibroblasts of the septal or portal interface, representing the prominent fibrogenic effectors, expressed RAGE in both fibrosis models.…”
Section: Discussionsupporting
confidence: 81%
“…Patients with chronic liver injuries were found to exhibit significantly higher hepatic RAGE expression levels [99] , and in NAFLD patients a correlation was detected between the severity of fibrosis and the patients' serum TAGE concentrations, indicating that RAGE and TAGE make significant contributions to the development of liver disease [23] . In addition, DM, which upregulates AGE synthesis and RAGE expression, has been found to accelerate the progression of fibrosis in a number of human liver conditions, including chronic hepatitis C and NAFLD [100] .…”
Section: The Inhibition Of Tage Synthesis: Acarbosementioning
confidence: 99%
“…Previous studies have demonstrated that RAGE-specific small interfering (si)RNA is able to inhibit the expression of the RAGE gene in primary rat hepatic stellate cells (HSCs), and may be able to inhibit the generation of profibrogenic cytokines (5)(6)(7). Furthermore, high expression levels of RAGE mRNA and protein have been observed in activated HSCs and CCl 4 -induced HF rats.…”
Section: Introductionmentioning
confidence: 99%